2011
DOI: 10.1088/0022-3727/44/32/325403
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contrast ratio of homogeneously aligned liquid crystal displays by controlling the surface-anchoring strength

Abstract: The dark state of homogeneously aligned liquid crystal displays (LCDs) associated with the in-plane switching of a LC director depends on their molecular ordering. We propose a new approach to reduce the light leakage in the dark state of homogeneously aligned LCDs. A very small amount of reactive mesogen (RM) is mixed with the LC material and polymerized at room temperature and also at a low temperature (−20 °C) to strengthen the surface-anchoring energy. The contrast ratio of the low-temperature cured cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This is the reason why an LC cell with a low RM concentration exhibits a low light leakage in the dark state. It was reported that the dark-state light leakage in a polymerstabilized IPS cell could be reduced by increasing the order parameter of the LC/polymer composites through low-temperature UV curing [20]. As shown in Figure 3b, low-temperature curing does not Table 1.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is the reason why an LC cell with a low RM concentration exhibits a low light leakage in the dark state. It was reported that the dark-state light leakage in a polymerstabilized IPS cell could be reduced by increasing the order parameter of the LC/polymer composites through low-temperature UV curing [20]. As shown in Figure 3b, low-temperature curing does not Table 1.…”
Section: Resultsmentioning
confidence: 93%
“…In particular, the curing temperature impacts the morphology of the polymer, which strongly affects the electro-optic properties of a polymer-stabilized LC cell. As the curing temperature decreases, the LC viscosity increases exponentially, which slows polymer diffusion [17][18][19][20]. Lower curing temperatures produce finer polymer networks and generate polymer-stabilized LCs with a smaller average distance between two neighboring bundles (or domain size).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] In order to overcome these limitations, the current photoaligning materials [18][19][20][21][22][23][24] need to be further improved. The recently introduced polymer-surface stabilisation by reactive mesogen (RM) [25,26] and photoaligning stabilisation [27][28][29][30][31] can be promising candidate methods for the enhancement of surface anchoring. Nevertheless, the switching stability of electro-optic characteristics of photoaligned IPS LCD with electric field stress still needs to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the RM molecules were aligned along the photoaligned LC orientation before UV exposure because of low RM concentration. [28,29] After filling, the cell with Case 3 was irradiated under unpolarised UV for 30 min with an intensity of 1.5 mW/cm 2 and then the RM molecules were polymerised at the interface of alignment layer and LC molecules along the placed original homogeneous state while an additional polymer layer was finally formed over photoaligning surface. [28][29][30] After sample fabrication, the switching textures of dark and white state of IPS cells were investigated using a polarised optical microscope (POM, Nikon DXM1200, Tokyo, Japan) in transmittance mode with and without voltage.…”
mentioning
confidence: 99%
See 1 more Smart Citation